PERKEMBANGAN PENDIDIKAN ISLAM MASA AWAL HINGGA LAHIRNYA KERAJAAN ISLAM DI ACEH, LEMBAGA, DAN TOKOHNYA - Martono La Moane; Bahaking Rama; Andi Achruh (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
The development of early Islamic education in Aceh, initially formed a Muslim community and then entered the royal palace and succeeded in forming early Islamic kingdoms, such as the kingdoms of Peureulek, Samudera Pasai, to the Kingdom of Aceh Darussalam. Islamic educational institutions are centered on villages and mosques, so that the plurality of Islamic education is through, meunasah, pekarangan, dayah, and jamiah. The concept of Islamic education at that time focused on the study of the yellow books, which were then adjusted to the level of Islamic education. Dayah scholars, in this case have an important role in Islamic education, such as Hamzah Fansuri, Samsuddin as-Sumatrani, Nuruddin ar- Raniri, and Abdur Rauf Singkel. In addition, Islamic boarding schools are not only centers of Islamic education, but also form individuals who are able to play a role in development, strongholds from colonial powers, and centers of community learning.